Influence of Principals’ Instructional Supervisory Practices on Learners’ Academic Performance in Kenya Certificate of Secondary Education in Kisii County, Kenya - Ololo, Thomas Odongo; Onditi, Mary Anyango; Mwebi, Benard (International Journal of Research and Innovation in Social Science (IJRISS), 2024)
Principals’ instructional supervision is very critical for quality academic performance. However, research studies have found out that inadequate training and heavy administrative workload has hindered most principals from carrying out their supervisory roles in schools effectively. In light of this scenario, this study investigated the Influence of Principals’ instructional supervisory practices on learners’ academic performance in Kenya Certificate of Secondary Education (K.C.S.E.) in Public Schools, in Kisii County, Kenya. The objective of this study was to: examine the influence of Principals’ instructional supervisory practices on learners’ academic performance in K.C.S.E. in Kisii County. This study was anchored on Karl Ludwig von Bertalanffy General Systems Theory. Mixed method research design of explanatory sequential type with a prioritized quantitative approach in phase one followed by qualitative approach in phase two was applied in the study. The target population was 4,691 participants which included: 340 Principals, 1360 Heads of Departments (H.O.Ds) and 2,991 teachers. A sample of 451 respondents participated in the study. The researcher used proportionate stratified random sampling technique to select 85 schools, 114 H.O.Ds and 252 teachers. Census sampling was used to select national and special schools while 85 Principals of the selected schools were purposefully sampled. Questionnaires and interview guides were used to collect quantitative and qualitative data respectively. Content validity, Criterion validity, Construct validity and Face validity, of the research instruments were ensured through evaluation by the University supervisors and other experts while internal consistency reliability was estimated by using Cronbach’s alpha coefficient formula which yielded alpha coefficient of over 0.7 which was considered adequate. Quantitative data were analysed using Statistical Package of Social Sciences (SPSS) Version 29 while qualitative data were analysed thematically and presented using direct quotes from the respondents and integrated with the findings of phase one. Descriptive statistics were presented in tables and graphs while inferential statistics were presented in terms of Pearson’s correlation coefficients, Anova and Regression coefficients. The study found out a weak positive insignificant influence between instructional supervisory practices (r=.025, p≤.05; 2 tailed) and learners’ academic performance in K.C.S.E. Therefore, the null hypothesis were upheld. These results were supported by Principals’ interviews which indicated that lack of intrinsic motivation to improve on performance and failure by the teachers to act on supervisory feedback have reduced impact of instruction supervision on academic performance. It is hoped that the findings of this study would provide information that would be a base for corrective measures towards the unexpected low academic performance in the study locale. The study recommended that further research should be done on influence of principals’ leadership skills development on academic performance in K.C.S.E.
Keywords: Mixed Methods; Explanatory Sequential; Inferential Statistics; Supervisory Feedback